Fake news jako front wojny w Ukrainie - Małecki, Łukasz (Studia Ukrainica Posnaniensia, 2023)
The present article analyzes the problem of Russian information aggression in the war against Ukraine, gives examples of dissemination of false information. Attention is also focused on the structure of fake news and the main currents of disinformation messages. The methods used to disseminate fake news and their impact on audiences are also analyzed.